A PREPARAÇÃO DE ELENCO QUE REVOLUCIONOU A INTERPRETAÇÃO DE ATORES NO BRASIL: FÁTIMA TOLEDO E O MÉTODO FT - BASEADO EM ATUAÇÕES REAIS. - Ismael Queiroz (TRF2, 2019)
Through a perspective between the interpretation of actors and the languages inserted in the context of dramatic art, this article exposes the capacity of options in technical and theoretical instruments that the Fátima Toledo Method (also called "FT Method") collaborates positively and unique, by form in most of the projects in which the preparation is found, making them peculiar. With this, all the writing here perceived can demystify negativities around the same Method and appearing as legitimate great ally of professionals of the arts and not artists. In the case of the actors, contributing to improve their ways of acting. Is congruent also for the expansion of the FT Method and its greater appreciation under the arts of the scene as a whole, surpassing the effectiveness already shown in successful films in the national cinema, and now from experiences practices assumed by the writer. It was essential to present a relation of the FT Method in new works, by another preparer, placing them as reference and research material. It is pointed out that the use of the tool in the interpretation of artists is increasingly important for the success of a film. One of the purposes is to cause a greater reflection on the rupture with stereotyped thoughts in the posture and relation of the "actor x character".